2018
DOI: 10.20517/2394-5079.2018.56
|View full text |Cite
|
Sign up to set email alerts
|

Thermal ablation of large unresectable hepatocellular carcinoma in cirrhotic patients

Abstract: Hepatocellular carcinoma (HCC) is one of the most common and lethal malignancies worldwide. Surgery is the mainstay of treatment, but less than 20%-30% of patients are good candidates. Actually, thermal ablation is considered the best treatment with curative intent for cirrhotic patients with unresectable HCC ≤ 3 cm. Unfortunately, radio frequency efficacy in obtaining the complete ablation of HCC nodules diminishes with increasing tumor size and local tumor progression is more frequent in larger nodules. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…This meta-analysis showed that LLR had a significantly better 5-year overall survival and better 1- and 3-year disease-free survival than RFA. Tumor size is one of the important factors in considering ablative treatment as the efficacy in complete ablation diminished with larger tumour size and local tumour progression was more frequent in larger tumours ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis showed that LLR had a significantly better 5-year overall survival and better 1- and 3-year disease-free survival than RFA. Tumor size is one of the important factors in considering ablative treatment as the efficacy in complete ablation diminished with larger tumour size and local tumour progression was more frequent in larger tumours ( 22 ).…”
Section: Discussionmentioning
confidence: 99%